Changes in vital signs, ventilation mode, and catecholamine use during intensive care aeromedical evacuation flights - Post, Janina; Maeckelburg, Marc Christoph; Jagel, Vitali; Sammito, Stefan (Frontiers in Public Health, 2023)
Introduction: Especially after (natural) disasters, local health systems are also destroyed or their ability to work is massively restricted. The transport of injured patients is therefore often necessary for further care. Numerous nations keep fixed-wing aircraft with intensiv-care capabilities available for secondary transport, but little data on the transport is available to date. Methods: An analysis of all flights with the German Air Force's intensive care fixed-wing-aircraft carried out in the context of humanitarian aid missions since 2002 with a focus on intubated patients was done. Results: A total of 38 patients were transported. Two patients had to be intubated on or during transport. There were significant changes in the necessary positive end-expiratory pressure (PEEP) and the fraction of inspired oxygen. Circulatory parameters did not change. Discussion: Overall, there are no clinically relevant deteriorations due to secondary transport with corresponding air transfers. Due to the hypobaric hypoxic conditions on board of all aircrafts, intubation in clinically borderline patients should be performed electively on the ground before flight.